The Influence of Profitability, Solvability, Firm Size, and Macroeconomics on Cost of Capital With Risk As a Moderating Variable on Multifinance Companies - Giovani Huiser Mangalindung; Adler Haymans Manurung; Jhonni Sinaga; Idel Eprianto (Dinasti Publisher, 2025)
This research was conducted to examine the effect of gross profit margin, return on asset, leverage, firm size, oil price, and exchange rate on the cost of capital with risk as a moderating variable of multifinance companies that go public. This research population publishes multifinance companies that go public for the 2016-2023 period. The sampling technique uses purposive sampling technique. Based on predetermined criteria the number of samples obtained by 12 companies. The type of data used in this study is secondary data using panel data regression analysis methods. The results showed gross profit margin has a positive and not significant effect on the cost of capital, leverage variable has a positive and significant effect on the cost of capital, return on asset and firm size have negative significant effect on the cost of capital, oil price has a positive significant effect on the cost of capital, exchange rate has a positive and not significant effect. Risk is able to moderate gross profit and firm size have positive and not significant effect on the cost of capital, whereas risk is able to moderate return on asset and leverage have negative and not significant effect on the cost of capital.